The Effect Of The Directed Quest Strategy For People With Kinetic Performance Difficulties In Learning The Volleyball Passing Skill For Students - Amer Rashed Shial, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
The purpose of this paper is to knowledge the effect of using the directed Quest strategy for those with  difficulties in kinetic performance in learning the skill of passing for volleyball for students. The  researcher used the experimental method for two groups (experimental and control). The research  sample consisted of (40) students from the second stage in the College of Physical Education and  Sports Sciences, University of Wasit, and the sample was divided The research was divided into two  equal groups, each group consisted of (20) students. The results of the research were summarized in the  presence of statistically significant differences between the average scores of the students in the post measurement for those who studied using the directed Quest strategy and those who studied using the  usual method. The differences were in favor of the experimental group, in light of the research results.  The researcher recommends using the directed Quest strategy for those with difficulties in kinetic  performance in learning the skill of volleyball passing for students, urging those in charge of teaching  to use the directed Quest strategy and encouraging them to employ it in teaching.